Lebanon Agriculture Sector Note : Aligning Public Expenditures with Comparative Advantage - World Bank (Washington, DC, 2013)
Agriculture is a small but stable part of the Lebanese economy. Approximately 20 to 25 percent of Lebanon's active population is involved in the sector in one way or another. This note is a synthesis of previous work written on agriculture development in Lebanon and related public expenditures in the sector. It starts with an overview of the agriculture sector in Lebanon and its role and contribution to the economy. Approximately eight percent of Lebanese households live below the poverty line. Among major economic sectors, agriculture has the highest rate of poverty. Over 20 percent of heads of households engaged in this sector are very poor. The North governorate is among the hardest hit areas with one in four agriculture workers likely to be poor. Agriculture sector development could play an important role in pro-poor growth. This note aims to focus on an agriculture sub-sector with significant growth potential. The Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis explains that Lebanon is relatively more competitive in fruits and vegetables than in cereals and livestock. First, Lebanon is a relatively water scarce country and livestock put a greater strain on water resources than fruits and vegetables. Second, cereals are a lower-value crop than fruits and vegetables, and have more volatile returns. Third, competitiveness in cereal markets requires producing in high volume. Lebanon is a small country that is very dependent on cereal imports, comprising roughly 83 percent of consumption. Thus, profitability is limited by a constraint on economies of scale. Moreover, making significant investments to reduce cereal import dependency may actually reduce food security by putting further strain on Government of Lebanon's (GoL's) fiscal balance, thereby limiting its ability to respond to food-price shocks. Livestock growth is also unattractive from a food security perspective because it would significantly increase domestic demand for cereals, increasing the country's exposure to market volatility.